Decolonization in St. Lucia : politics and global neoliberalism, 1945-2010 - Joseph, Tennyson S. D. (Caribbean studies series (Jackson, Miss.), 2011)
Joseph explores the impact of global transformation upon the independent experience of St. Lucia and argues that the island's formal decolonisation roughly coincided with the period of the rise of global neo-liberalism hegemony. Consequently, the concept of 'limited sovereignty' became the defining feature of St. Lucia's understanding of the possibilities of independence. Central to the analysis is the tension between the role of the state as a facilitator of domestic aspirations on one hand, and as a facilitator of global capital on the other.